Przyrządzanie wizerunku Murzyna w antologii „Niam niam” Edwarda Kozikowskiego i Emila Zegadłowicza - Wojda, Dorota (Wydawnictwo Naukowe UAM, 2013)
The article presents an interpretation of texts published in 1923 as a collection of translated African poetry, which was in fact a literary mystification. The concepts of postcolonial criticism are used to analyze some racial stereotypes that have been updated by the authors of the performance and to demonstrate how they project their own ideas of regionalism and primitivism on the characters in their poems, thereby committing an act of symbolic anthropophagy
Preparing the image of a black person in the anthology Nyam nyam by Edward Kozikowski and Emil Zegadłowicz